Analysis of institutional policies on the personality and quality of human resources in maintaining teacher productivity and motivation during the pandemic - Rahayu, Widya Adhariyanty; Kala’lembang, Adriani (Management and Entrepreneurship: Trends of Development, 2022)
Institutions are an important part in terms of employment for both educated and uneducated workers. Policies in increasing productivity and motivation play an important role in education management in Indonesia, especially in Malang Regency. This study used a qualitative research method with a descriptive approach. The data obtained came from interviews, personal notes, questionnaires, and documents needed to conduct research. This study resulted in an institution policy on the quality of work of teachers and staff in increasing productivity in the post-pandemic period. The results show that the provision of policies in the form of good intrinsic and extrinsic motivation and excellent rewards in supporting the performance of teachers in educational institutions. In the implementation to improve teacher performance, the efforts made by the principal are a) Training by the field of study offered. b) Provide motivation, and inspiration in achieving goals. c) Giving confidence in doing something. d) Appreciate the work of teachers in educating students. JEL Classification: J08, M54.